The Ebenezer Bible College Library a case study of its growth and development - Naraval, Thelma F.; Picache, Ursula G.; Tan, Samuel K. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1976)
The purpose of this study was to make a careful study of the growth and development of the Ebenezer Bible College Library and its collections to determine how it contributes to the preservation of a conservative intellectual orientation of the Christian and Missionary Alliance constituency and to find out its role in the education of Filipino ministers. The study attempted (1) to determine the means by which the library collection was developed; (2) to show that the collection of the Ebenezer Library has been greatly affected by the conservative policies and aims of the missionary organization; and (3) to provide a basis for the study of how Filipiniana materials in the library can help in the development of a Filipino orientation among the ministers in training. Likewise, this can serve as guide in the study of other theological libraries.
All available materials concerning the Ebenezer Bible College Library at the Mission and National Church Headquarters in Zamboanga City and in all offices at the Ebenezer Bible College, including the Ebenezer Library, was examined. Ministers and missionaries were also interviewed and contacts were made with individuals here and abroad through correspondence. A critical analysis of the history of The Christian and Missionary Alliance Churches of the Philippines, Inc., the Ebenezer Bible College, the organization and administration of the Ebenezer Library and its collections was made.
The structure also shows that the library staff is a repository of conservatism since, generally, graduates of the Bible College and wives of school staff are given the positions. A detailed study of the collection revealed that the library holds a specialized collection of religious books which preserves a distinct doctrinal orientation, a Conservative doctrinal position. Most of the books were received as gifts; only 29 percent were purchased. Based on the result of the classification made by three subject specialists, it can be stated that 95 percent of the classified religious collection are conservative and only 5 percent are Liberal. The collection is deficient in secular and Filipiniana materials.
It is concluded that since the Ebenezer Bible College had been administered by missionaries for several years and they are still influencing the academic, spiritual, and financial aspects of the school, the library policies, although unwritten, have remained conservative. The policies of the missionary organization naturally affected the library. It is also concluded that the lack of written book selection and acquisition policies of the library may have resulted in the unbalanced collection of the library. This situation indicates that the education of the Bible student may not be well-rounded. Finally, it is concluded that since the Filipiniana collection is very deficient, then the inculcation of Filipinistic values on the Bible students has been somehow jeopardized. The intention has been to train the Bible student as a minister, but the curriculum and the library collection seem to fail to prepare him for a Filipino ministry.
Typescript.
Vita.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Ebenezer Bible College. Library